On an application of sequential bayesian techniques for estimating the fatality rate of Dengue in Malaysia - Kamarulzaman Ibrahim; Abdul Aziz Jemain (Universiti Kebangsaan Malaysia, 1997)
Dengue is one of the main factors of mortality of inhabitants in the region of South East Asia. Malaysia is one of the countries which is facing a high incidence of dengue, particularly in the 70's and early 80's. The Ministry of Health has taken various measures in order to reduce the dengue epidemic. These include educating people about dengue and conducting research such as investigation of factors that influence the epidemic of dengue. In this study, a sequential Bayesian approach is applied to data of the proportion of death due to dengue over the period from 1982 to 1992. In the sequential Bayesian approach, the data for the year 1982 becomes the prior information for the 1983 data and so on. The data for the different periods are combined in a chronological manner until the final posterior distribution of the proportion of death due to dengue is obtained. It is found that the overall proportion is 0.59% and its standard deviation is 0.00002%.